Audition - Zwartjes, Frans (The Netherlands, 1973)
"Audition" portrays a good example of a film with a nice music band. The film is a visual improvisation between camera and actors, almost without a story-line - a man watches and listens to a singing woman, while another woman watches and mainly in exciting black-and-white images.
Black and White
Silent
Verzio Film Festival Submission
Keywords: Experimental films